Praktik Metta Bhavana dalam Upaya Meningkatkan Kesehatan Mental: Studi Kasus pada Jemaat Vihara Jakarta Dhammacakkha Jaya, Sunter - Oe Mardi, Ega Mutiara; Nuh HS, Moh.; Nadroh, Siti (Inklusiva: Jurnal Studi Agama-Agama, 2025)
This research examines the influence of Metta Bhavana practice in improving mental health among the congregation of Jakarta Dhammacakka Jaya Sunter Monastery. The aim is to understand the role of Metta Bhavana in the spiritual life of the congregation, which makes it an important part of their religious practice. This research uses a qualitative approach with William James' theory of religious experience and contextual pragmatism. James' theory focuses on how individuals experience and interpret spiritual experiences, while pragmatism evaluates the benefits of practices based on practical effects in daily life. These two theories were used to analyze the impact of Metta Bhavana on the mental health of the community, including personal, emotional, and social aspects. Data were collected through field observations and interviews with seven resource persons: a monastery administrator, a bhante, and five congregants. The results showed that Metta Bhavana helped the community to overcome various mental health problems arising from life issues such as failure, household disharmony, and future anxiety. The meditation practice was shown to reduce stress, improve mental well-being, and strengthen social relationships among community members. Metta Bhavana has a positive impact on the personal, emotional, and life-transforming aspects of the community, in line with William James' theory. This research can serve as a basis for developing broader meditation practices to support the mental and spiritual health of congregants.